1989
DOI: 10.1099/00221287-135-5-1291
|View full text |Cite
|
Sign up to set email alerts
|

The Penetration of Antibiotics into Aggregates of Mucoid and Non-mucoid Pseudomonas aeruginosa

Abstract: ~~ ~ ~Cells of mucoid and non-mucoid Pseudomonas aeruginosa in colonies were at least onethousandfold less sensitive to the antibiotics tobramycin or cefsulodin than were cells of the same bacteria in dispersed suspension. We did not detect any difference between the mucoid form and the non-mucoid form in the antibiotic sensitivity of colonies, from which we infer that the exopolysaccharide of the mucoid form does not contribute to colony-resistance by forming a barrier to antibiotic diffusion. Mathematical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 45 publications
6
129
1
2
Order By: Relevance
“…Overproduction of alginate could be an important contributory factor for Alg þ PAOmucA22 persistence and virulence. This study supports previous inferences that alginate is a virulence factor that contributes to bacterial adherence and persistence (Marcus & Baker, 1985;Ramphal & Pier, 1985;Doig et al, 1987), formation of microcolony and biofilm growth (Høiby, 1975;Lam et al, 1980;, inhibition of PMN chemotaxis (Stiver et al, 1988;Pedersen et al, 1990), suppression of lymphocyte and PMN function (Pedersen et al, 1990;Mai et al, 1993), formation of a physical barrier to the immune system and antibiotics (Nichols et al, 1989;Evans et al, 1991;Hoyle & Costerton, 1991;Mathee et al, 1994) and resistance to opsonic killing by PMNs and macrophages (Meshulam et al, 1984;Cabral et al, 1987;Jensen et al, 1990;.…”
Section: Diagnostic Value Of Il4 Levelssupporting
confidence: 78%
“…Overproduction of alginate could be an important contributory factor for Alg þ PAOmucA22 persistence and virulence. This study supports previous inferences that alginate is a virulence factor that contributes to bacterial adherence and persistence (Marcus & Baker, 1985;Ramphal & Pier, 1985;Doig et al, 1987), formation of microcolony and biofilm growth (Høiby, 1975;Lam et al, 1980;, inhibition of PMN chemotaxis (Stiver et al, 1988;Pedersen et al, 1990), suppression of lymphocyte and PMN function (Pedersen et al, 1990;Mai et al, 1993), formation of a physical barrier to the immune system and antibiotics (Nichols et al, 1989;Evans et al, 1991;Hoyle & Costerton, 1991;Mathee et al, 1994) and resistance to opsonic killing by PMNs and macrophages (Meshulam et al, 1984;Cabral et al, 1987;Jensen et al, 1990;.…”
Section: Diagnostic Value Of Il4 Levelssupporting
confidence: 78%
“…However, the concentration of antibiotics and biocides required to kill bacteria residing within the biofilm matrix can be 500 to 5,000 times those needed to kill planktonic cells of the same species [17,18,21,35,[71][72][73][74]. It is not known, however, whether the observed recalcitrance of bacteria in the biofilm mode of growth to antimicrobial challenge is also true for electrically induced toxicity and whether the biofilm provides a similar tolerance advantage to this approach.…”
Section: The Bioelectric Effectmentioning
confidence: 86%
“…Hoyle and Costerton (1991) suggested that the barrier to drug penetration formed by the exopolysaccharide and the low growth rate of bacteria in biofilms were related to drug resistance. In contrast, Nichols et al (1989) reported that alginate, an exopolysaccharide of mucoid-type P. aeroginosa, had a very limited effect in reducing drug penetration. It therefore seems that the mechanism resulting drug resistance on biofilm-forming organisms remains unclear.…”
Section: Limited Diffusion Through the Biofilmmentioning
confidence: 92%
“…Cells of mucoid and non-mucoid Pseudomonas aeroginosa in colonies were at least one-thousandfold less sensitive to the antibiotics tobramycin or cefsulodin than were cells of the same bacteria in suspension. No difference was detected between the mucoid form and the non-mucoid form in the antibiotic sensitivity of colonies, from which it was concluded, that the exopolysaccharide of the mucoid form does not contribute to colony-resistance by forming a barrier to antibiotic diffusion (Nichols et al, 1989).…”
Section: Limited Diffusion Through the Biofilmmentioning
confidence: 95%